IMPLEMENTASI LESSON STUDY UNTUK MENINGKATKAN MINAT BELAJAR MAHASISWA MELALUI METODE PEMBELAJARAN SEMINAR GROUP - Lukmanul Akhsani; Kusno Kusno; Ahmad Ahmad (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2014)
. Lesson Study (LS) is the learning of assessment activities carried out by a group of teachers / faculty collaborative and sustainable to test and improve the effectiveness of learning. In this study, the implementation of lesson study to improve student interest in learning through the learning method Seminars Group. The results obtained by analysis of the average increase student interest in learning. Cycle 1 gained an average interest of students 67, 86 in the category of high interest in learning. In the first cycle of the findings of the observer focused on seating position make it difficult for the observer to move and students still do not concentrate on learning. Seat that is positioned in groups. Cycle 2 gained an average of 70.78 in the category of student interest high interest in learning. In Cycle 2 focused on the position of the seat. Apparently after the seat is positioned to the observer, the motion less students, so many students are easily sleepy and easier to jaw, with no attention to the lecturer. Cycle 3 gained an average of 72.59 students' interest in the category of high interest. In the do cycle 3, the observer gain some findings that many students were late, and there are still some students who own story. This is possible because they are too short presentation and question focus. Suggestions observer, lecturer models the moderator in the learning process. Cycle 4 gained an average of 72.71 in the category of student interest high interest in learning. Learning is in conformity with the plan, but there are still students who do the work of other subjects. This is a model professor responded by asking questions that make students think, re-concentration of students with learning again.